1997
DOI: 10.1542/peds.100.3.e2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Effects of a Competitive Road Race in Trained Child Runners

Abstract: ABSTRACT.Background. Animal studies and investigations of adult endurance athletes indicate a transient depression of myocardial function after prolonged highintensity exercise.Purpose. To determine whether a similar decrease is observed in child distance runners after a 4-km competitive road race.Methods. Anthropometric measures, resting M-mode echocardiograms, maximal cycle exercise tests with estimation of cardiac output, and electrocardiograms were performed before a 4-km road race in nine run-trained boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
(14 reference statements)
1
5
0
2
Order By: Relevance
“…Rowland et al (24) reported no changes in LV function after a 4-km run (~15 min) in trained boys; however, the duration was considerably shorter than that used in the cunent study. Within the present study, postexercise changes in LV systolic (EF) and diastolic (E:A) function were statistically significant but small and noncumulative with EF after exercise still within normal limits (19,35).…”
Section: Functionmentioning
confidence: 83%
“…Rowland et al (24) reported no changes in LV function after a 4-km run (~15 min) in trained boys; however, the duration was considerably shorter than that used in the cunent study. Within the present study, postexercise changes in LV systolic (EF) and diastolic (E:A) function were statistically significant but small and noncumulative with EF after exercise still within normal limits (19,35).…”
Section: Functionmentioning
confidence: 83%
“…Volume depletion produced reductions in both diastolic and systolic chamber dimensions such that FS% was unchanged. Studies of human patients treated with furosemide, 32,33 hemodialysis, 34 or dehydrated by exercise 35 demonstrated reduced diastolic LV chamber dimension without concomitant effects on systolic chamber dimension. However, phlebotomized infants 36 and pigs 16,37 develop reductions in both LV diastolic and systolic dimensions.…”
Section: Discussionmentioning
confidence: 98%
“…By responses to a questionnaire, none of the runners nor controls had yet experienced pubertal signs of voice change, appearance of pubic hair, or growth spurt. The runners were included in a previous report of echocardiographic changes following a road race (19). and the controls were involved in a study comparing cardiovascular responses to exercise in children and adults (22).…”
Section: Methodsmentioning
confidence: 99%